(untitled) (DARYAFT, 2022)
Binary thinking is a way of understanding the world around. It is used to oversimplify the complex situations and reality. Dichotomous way of thinking usually uses an innate hierarchy of the tow objects or situations it makes binary of Urdu Novel since its inception used binary opposites to foreground the characters it likes or dislikes. In this article Critical Discourse Analysis (CDA) is used as a method to underscore the binary thinking in Urdu Novel. The article maps the social conditions of discourse and shows how these conditions were determining the discourse of Urdu Novel. Urdu Novel made many binaries of characters, social categories and race etc. Only two binaries, i.e. same gender and race are analyzed here.